Strategi TVRI Medan dalam Meningkatkan Kualitas Siaran di Era 4.0 - Paralihan, Hotmatua; Zuraida, Lia; Sebayang, Khairunnisa; Khairani, Dita Nabila; Zharifah, Shafira Putri; Septika, Ghina (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research examines TVRI Medan's strategies for improving broadcast quality in the era of 4.0 using qualitative descriptive qualitative research methods, data collection techniques such as observation and interviews. The results show that TVRI Medan's strategies for enhancing broadcast quality in the 4.0 Era involve the use of the latest technology, development of digital platforms, collaboration with educational institutions and local creative agencies, and more active interaction with the audience. TVRI Medan's success in improving broadcast quality is attributed in part to the availability of adequate broadcasting technology support. This significantly influences the quality of broadcast programs, as the general public tends to prefer media with high-quality content. TVRI continues to enhance quality to adapt to changing media trends, improve the appeal and quality of broadcasts, and develop innovative content.